Specific amino acid supplementation rescues the heart from lipid overload-induced insulin resistance and contractile dysfunction by targeting the endosomal mTOR-v-ATPase axis - Shujin Wang; Francesco Schianchi; Dietbert Neumann; Li-Yen Wong; Aomin Sun; Frans A. van Nieuwenhoven; Maurice P. Zeegers; Agnieszka Strzelecka; Umare Col; Jan F.C. Glatz; Miranda Nabben; Joost J.F.P. Luiken (Elsevier, 2021)
Objective: The diabetic heart is characterized by extensive lipid accumulation which often leads to cardiac contractile dysfunction. The underlying mechanism involves a pivotal role for vacuolar-type H+-ATPase (v-ATPase, functioning as endosomal/lysosomal proton pump). Specifically, lipid oversupply to the heart causes disassembly of v-ATPase and endosomal deacidification. Endosomes are storage compartments for lipid transporter CD36. However, upon endosomal deacidification, CD36 is expelled to translocate to the sarcolemma, thereby inducing myocardial lipid accumulation, insulin resistance, and contractile dysfunction. Hence, the v-ATPase assembly may be a suitable target for ameliorating diabetic cardiomyopathy. Another function of v-ATPase involves the binding of anabolic master-regulator mTORC1 to endosomes, a prerequisite for the activation of mTORC1 by amino acids (AAs). We examined whether the relationship between v-ATPase and mTORC1 also operates reciprocally; specifically, whether AA induces v-ATPase reassembly in a mTORC1-dependent manner to prevent excess lipids from entering and damaging the heart. Methods: Lipid overexposed rodent/human cardiomyocytes and high-fat diet-fed rats were treated with a specific cocktail of AAs (lysine/leucine/arginine). Then, v-ATPase assembly status/activity, cell surface CD36 content, myocellular lipid uptake/accumulation, insulin sensitivity, and contractile function were measured. To elucidate underlying mechanisms, specific gene knockdown was employed, followed by subcellular fractionation, and coimmunoprecipitation. Results: In lipid-overexposed cardiomyocytes, lysine/leucine/arginine reinternalized CD36 to the endosomes, prevented/reversed lipid accumulation, preserved/restored insulin sensitivity, and contractile function. These beneficial AA actions required the mTORC1-v-ATPase axis, adaptor protein Ragulator, and endosomal/lysosomal AA transporter SLC38A9, indicating an endosome-centric inside-out AA sensing mechanism. In high-fat diet-fed rats, lysine/leucine/arginine had similar beneficial actions at the myocellular level as in vitro in lipid-overexposed cardiomyocytes and partially reversed cardiac hypertrophy. Conclusion: Specific AAs acting through v-ATPase reassembly reduce cardiac lipid uptake raising the possibility for treatment in situations of lipid overload and associated insulin resistance.